2007
DOI: 10.2337/dc07-0748
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity, Vascular Function, and Iron Stores in Voluntary Blood Donors

Abstract: OBJECTIVE -Reduced iron stores after blood donation are associated with improved vascular function and decreased cardiovascular risk. We sought to determine whether irondependent changes in glucose metabolism may contribute to improved vascular function in blood donors.RESEARCH DESIGN AND METHODS -We conducted a prospective cross-sectional study in 21 high-frequency blood donors (more than eight donations in the last 2 years) and 21 low-frequency blood donors (one to two donations in the last 2 years) aged 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
0
19
2
Order By: Relevance
“…9 Likewise, many investigations have evaluated the impact of blood donation frequency per year on SF levels, and have reported that ferritin concentrations diminished markedly with increased blood donations. 8,[19][20][21][22] In contrast to our findings regarding Hb levels, no correlation was observed between levels of Hb and donation frequency in male blood donors in some other studies. 15,20,21,23 The difference between the present study and these other relevant investigations may be explained by differences in the baseline Hb values, sensitivity and specificity of laboratory measurements, minimum donation interval, age range, food patterns and ethnic types of the participants in these surveys.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…9 Likewise, many investigations have evaluated the impact of blood donation frequency per year on SF levels, and have reported that ferritin concentrations diminished markedly with increased blood donations. 8,[19][20][21][22] In contrast to our findings regarding Hb levels, no correlation was observed between levels of Hb and donation frequency in male blood donors in some other studies. 15,20,21,23 The difference between the present study and these other relevant investigations may be explained by differences in the baseline Hb values, sensitivity and specificity of laboratory measurements, minimum donation interval, age range, food patterns and ethnic types of the participants in these surveys.…”
Section: Discussioncontrasting
confidence: 56%
“…Unlike our study, it has also been shown that indicators of iron status other than SF do not present contrasts between frequent and infrequent blood donors. 22 In our study, the minimum Hb cutoff for blood donation found that the Hb levels of multi-time donors did not notably contrast with those of donors who were giving blood for the first time. 25 Likewise, concordant with our results, other studies found that the SF levels in male donors had a negative significant relationship with the number of donations.…”
Section: Discussionmentioning
confidence: 89%
“…Increased insulin sensitivity and decreased insulin secretion were observed in blood donors compared with non-donors [90]. Decreased serum ferritin in highly frequent blood donors (≥8 per 2 years) was associated with increased flow-mediated dilation, in comparison with infrequent donors (1-2 per 2 years), but no improvement of insulin sensitivity was observed [91]. Ten healthy blood donors receiving 4-weekly phlebotomy (500 ml) showed significantly reduced insulin and glucose by 39% and 19% respectively in an OGTT.…”
Section: Lowering Body Iron Storesmentioning
confidence: 66%
“…In a 3-year prospective analysis, ferritin and transferrin levels were associated with hyperinsulinemia and hyperglycemia [35]. In the other study, blood donation was simultaneously associated with increased insulin sensitivity and decreased iron stores in healthy people [36], whereas, Zheng et al [37] showed that the mechanisms linking blood donation to improved vascular function were not related to changes in glucose metabolism.…”
Section: Discussionmentioning
confidence: 96%